Behavioural-centerd workplace safety part II - Lee, Cheng Han (2014)
In recent years, workplace safety in Singapore is being thrust further into the spotlight. This project examines the efficacies of two theories, namely the Theory of Communicative Action and the Theory of Planned Behaviour on workplace safety By incorporating these two theories, we developed a to map out the flow a Speech act works and the factors that contribute to a successful Speech Act in the workplace.